Antiplatelet efficacy of P2Y12 inhibitors (prasugrel, ticagrelor, clopidogrel) in patients treated with mild therapeutic hypothermia after cardiac arrest due to acute myocardial infarction - Bednar, Frantisek; Kroupa, Josef; Ondrakova, Martina; Osmancik, Pavel; Kopa, Milos; Motovska, Zuzana (Journal of thrombosis and thrombolysis, 2016)
Survivors after cardiac arrest (CA) due to AMI undergo PCI and then receive dual antiplatelet therapy. Mild therapeutic hypothermia (MTH) is recommended for unconscious patients after CA to improve neurological outcomes. MTH can attenuate the effectiveness of P2Y12 inhibitors by reducing gastrointestinal absorption and metabolic activation. The combined effect of these conditions on the efficacy of P2Y12 inhibitors is unknown. We compared the antiplatelet efficacies of new P2Y12 inhibitors in AMI patients after CA treated with MTH. Forty patients after CA for AMI treated with MTH and received one P2Y12 inhibitor (clopidogrel, prasugrel or ticagrelor) were enrolled in a prospective observational single-center study. Platelet inhibition was measured by VASP (PRI) on days 1, 2, and 3 after drug administration. In-hospital clinical data and 1-year survival data were obtained. The proportion of patients with ineffective platelet inhibition (PRI > 50 %, high on-treatment platelet reactivity) for clopidogrel, prasugrel, and ticagrelor was 77 vs. 19 vs. 1 % on day 1; 77 vs. 17 vs. 0 % on day 2; and 85 vs. 6 vs. 0 % on day 3 (P < 0.001). The platelet inhibition was significantly worse in clopidogrel group than in prasugrel or ticagrelor group. Prasugrel and ticagrelor are very effective for platelet inhibition in patients treated with MTH after CA due to AMI, but clopidogrel is not. Using prasugrel or ticagrelor seems to be a more suitable option in this high-risk group of acute patients.
Keywords: senioři; Heart Arrest; terapeutická hypotermie; srdeční zástava; ticagrelor; Prasugrel Hydrochloride; Middle Aged; mužské pohlaví; infarkt myokardu; Ticagrelor; Prasugrel; adenosin; Prospective Studies; Hypothermia, Induced; Ticlopidine; Purinergic P2Y Receptor Agonists; Myocardial Infarction; prasugrel hydrochlorid; ženské pohlaví; Clopidogrel; Adenosine; Humans; prospektivní studie; Myocardial infarction; Cardiac arrest; agonisté purinergního receptoru P2Y; lidé středního věku; Hypothermia; Female; tiklopidin; Aged; klopidogrel; lidé; Male